2020
DOI: 10.1111/mam.12197
|View full text |Cite
|
Sign up to set email alerts
|

Only the largest terrestrial carnivores increase their dietary breadth with increasing prey richness

Abstract: 1. Animals should adapt their foraging habits, changing their dietary breadth in response to variation in the richness and availability of food resources. Understanding how species modify their dietary breadth according to variation in resource richness would support predictions of their responses to environmental changes that alter prey communities. 2. We evaluated relationships between the dietary breadth of large terrestrial carnivores and the local richness of large prey (defined as the number of species).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 87 publications
(149 reference statements)
1
42
0
Order By: Relevance
“…Across their distributional range, jaguars have been documented to take at least 111 wild species [ 19 ]. They are widely considered to be opportunistic predators, displaying greater dietary breadth (increased generalism) with increasing prey richness [ 20 ]. However, generalist feeding behaviour at the distributional level may reflect specialisations at the population level (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Across their distributional range, jaguars have been documented to take at least 111 wild species [ 19 ]. They are widely considered to be opportunistic predators, displaying greater dietary breadth (increased generalism) with increasing prey richness [ 20 ]. However, generalist feeding behaviour at the distributional level may reflect specialisations at the population level (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have been combined to address conservation questions about individual carnivore prey preferences (Hayward & Kerley, 2008) and diet variation across abiotic gradients (Bojarska & Selva, 2012; Virgos et al., 1999), and to conduct multispecies macroecological and macroevolutionary analyses. However, such analyses are often taxonomically and morphologically limited, such as vulnerability of felids to prey loss (Sandom et al., 2017) or dietary breadths of large (>14.5 kg) Carnivora (Ferretti et al., 2020). Collating and making openly accessible diet data across taxonomic groups of carnivorous mammals across wider body mass ranges would allow further conservation questions to be answered, and open up research avenues in macroevolution and macroecology.…”
Section: Introductionmentioning
confidence: 99%
“…Jaguars, alongside pumas ( Puma concolor ; IUCN: least concern; [ 53 ]), are the largest predators in the region and their presence elsewhere has been associated with prey biomass and availability [ 22 , 54 – 56 ]. However, some studies have also found that prey richness can be related to large carnivore richness [ 57 ], occupancy [ 15 ], or dietary niche breadth [ 58 ].…”
Section: Introductionmentioning
confidence: 99%